Evaluating the effects of a wearable assistive device (WAD) on decreasing lumbar muscles activity during static holding tasks: EMG analysis and biomechanical modeling - Hadi Heydari; Maryam Hoviattalab; Mahmood Reza Azghani; Masoud Ramezanzadeh; Mohamad Parnianpour (Vesnu Publications, 2011)
Introduction: One of the most common diseases associated with musculo-skeletal ailment is low back pain which is epidemic among general public. If manual tasks are performed inappropriately by workers at workplaces, it may cause back pain in the lumbar spine. In recent years, a variety of assistive devices has been developed and employed to utilize a passive force generator which has been proved to be effective in decreasing lumbar moments and the force requirements by Erector Spinae muscles. In forward flexion, trunk muscles sustain a balance between the weight of upper body and external loads. Because of small moment arm of these muscles, they can create great forces that may lead to high intradiscal pressure and cause disc injury. The aim of this paper is to present a new Wearable Assistive Device that decreases trunk muscle activity during static holding task. The performance of this device is simulated biomechanically with link-segment model. Materials and Methods: Using ANYBODY software, compressive and shearing forces and also muscle activity of Lumbar were determined. To validate the results, electromyography (EMG) of fifteen males' muscles participated in the study was analyzed.  Results: Results of link-segment model indicated that there was a reduction in the Lumbar moment by 15- 23% using WAD. Moreover ANYBODY model demonstrated that compressive and shearing forces decreased by 24% and 29% respectively in average and muscle activities decreased by 18-25%, too. Statistical analysis indicated that normalized electromyography of right and left Lumbar, Thoracic Erector Spinae and Latissimus Dorsi muscles had significantly decreased  by 21.9%, 20.4%, 23.6%, 20.4%, 23.7%, and 16.7% (p<0.05) respectively and electromyography of right and left External Oblique, Internal Oblique and Rectus Abdominus muscles had underwent a significant change. (p<0.05)   Keywords: Wearable Assistive Device (WAD), Lumbar moments, Muscle activity, Biomechanical model, EMG